A study of the public elementary school libraries in Manila - Parayno, Emilda A.; Furbeyre, Mae L.; Pastrana, Cecillia C. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1969)
Surveys library resources and services fifty-four public elementary schools in the City of Manila in 1967-1968. Findings are compared and evaluated against prescribed school library standards.Library resources and services of the libraries surveyed are found to be sub-standard. Problems and needs of public school librarians are presented. Recommendations are given to improve and upgrade public elementary school libraries in Manila.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: School libraries -- Philippines -- Manila